SARS-CoV-2-Indigenous Microbiota Nexus: Does Gut Microbiota Contribute to Inflammation and Disease Severity in COVID-19? - Chattopadhyay, Indranil; Shankar, Esaki M. (Frontiers in Cellular and Infection Microbiology, 2021)
Gut microbiome alterations may play a paramount role in determining the clinical outcome of clinical COVID-19 with underlying comorbid conditions like T2D, cardiovascular disorders, obesity, etc. Research is warranted to manipulate the profile of gut microbiota in COVID-19 by employing combinatorial approaches such as the use of prebiotics, probiotics and symbiotics. Prediction of gut microbiome alterations in SARS-CoV-2 infection may likely permit the development of effective therapeutic strategies. Novel and targeted interventions by manipulating gut microbiota indeed represent a promising therapeutic approach against COVID-19 immunopathogenesis and associated co-morbidities. The impact of SARS-CoV-2 on host innate immune responses associated with gut microbiome profiling is likely to contribute to the development of key strategies for application and has seldom been attempted, especially in the context of symptomatic as well as asymptomatic COVID-19 disease.